Antioxidant effect of Morus nigra on Chagas disease progression - Montenote, Michelly Cristina; Wajsman, Vithor Zuccaro; Konno, Yoichi Takaki; Ferreira, Paulo Cesar [UNESP]; Goncalves Silva, Regildo Marcio [UNESP]; Silva Therezo, Altino Luiz; Silva, Luciana Pereira; Alves Martins, Luciamare Perinetti (Inst Medicina Tropical Sao Paulo, 2017)
Considering the widespread popular use of Morus nigra and the amount of scientific information on its antioxidant and anti-inflammatory activity, the effectiveness of this phytotherapeutic compound in the parasitemia progression during the acute phase of Chagas disease and its role in the development of the inflammatory process as well as its effects on the oxidative damage in the chronic phase of infection were evaluated. Thus, 96 male Swiss mice were randomly divided into eight groups, four groups were uninfected controls, and four groups were intraperitoneally infected with 5.0 x 10(4) blood trypomastigotes forms of T. cruzi QM2 strain. Four batches composed of one uninfected and one infected group were respectively treated with 70% alcohol solution and 25 mu L, 50 mu L and 75 mu L of the phytotherapeutic compound. Levels of antioxidant elements (TBARS, FRAP, GSH and Sulfhydryl groups) were measured in plasma samples. The phytotherapeutic compound's antioxidant activity was measured by polyphenol and total flavonoid quantification, DPPH, NO, and FRAP method. Our results showed that the vehicle influenced some of the results that may have physiological relevance in Chagas disease. However, an important action of M. nigra tincture was observed in the progression of Chagas disease, since our results demonstrated a reduction in parasitemia of treated groups when compared to controls, especially in the group receiving 25 mu L. However, in the chronic phase, the 50-mu L dosage presented a better activity on some antioxidant defenses and minimized the tissue inflammatory process. Results indicated an important action of M. nigra tincture on the Chagas disease progression.
Keywords: Phytotherapy; Herbal medicine; Herbal compounds; Phytotherapeutic compound; Plant extracts; Parasitic diseases; Blackberry; Oxidative stress